The Relationship between Electrical Stapedius Reflex Thresholds and Behaviorally Most Comfortable Levels in Experienced Cochlear Implant Users - ÇİPRUT, AYŞE AYÇA (AVES, 2020)
OBJECTIVES: Programming the cochlear implant's speech processor with subjective methods in young, uncooperative children is difficult. Since young children cannot provide adequate feedback to the clinician, objective methods which do not require patient's response were often used. Electrical Stapedius Reflex Test is one of the most common procedures used. The goal of this study was to investigate the relationship between electricalstapedius reflex thresholds and behaviorally most comfortable levels in experienced cochlear implant users. MATERIALS and METHODS: The patients implanted with two brands of cochlear implants were compared in terms of electrical stapedius reflex thresholds versus most comfortable levels. Speech tests results were also compared between the two groups. 46 cochlear Implanted patients who had at least 1 year of cochlear implant experience were included in the study. 28 patients were implanted with Nucleus, 18 patients with Med-El devices. RESULTS: Moderate correlations were obtained between Electrical Stapedius Reflex (ESR) thresholds and the comfort (C) levels in Nucleus users; higher correlations were obtained for Med-El patients. ESR thresholds were present at higher levels than the most comfortable and the comfort (MCUC) levels in both Nucleus and Med-El users. No significant difference was obtained between the two groups in terms of speech tests. CONCLUSION: ESR test can be very informative for programming young and uncooperative patients.
Keywords: Electrical Stapedius Reflex Test; cochlear implant; MCL; comfort level; DYNAMIC-RANGE; CHILDREN